Interventions to Reduce Intra-Operative and Post-Operative Pain Associated with Routine Dental Procedures in Children: A Systematic Review and Meta-Analysis - Mohammed A. Alzubaidi; Bernadette K. Drummond; Jianhua Wu; Adam Jones; Vishal R. Aggarwal (MDPI AG, 2024)
Objective: implementing appropriate pharmacological and non-pharmacological interventions to alleviate pain related to routine dental procedures in paediatric patients could enhance children's ability to manage dental care. The aim of this review was to investigate the effectiveness of and provide recommendations for interventions that can be used to reduce intra-operative and post-operative pain associated with routine paediatric dental procedures. Methods: A systematic review of randomised controlled clinical trials (RCT) was conducted. Multiple electronic databases were systematically searched. The Cochrane risk-of-bias tool for RCTs was used to evaluate the quality of the included studies. A meta-analysis was performed to determine the effectiveness of the interventions using the Cohen's d standardised mean differences (SMD) and 95% confidence intervals (CIs) for continuous outcomes. The GRADE tool was used to assess the certainty of evidence to make recommendations. Results: The review included forty-five RCTs comprising 3093 children. Thirty-seven RCTs were included in the meta-analysis, which showed the effectiveness of behavioural interventions (SMD = −0.50, 95% CI −0.83 to −0.18), mechanoreceptor and thermal receptor stimulation (SMD = −1.38, 95% CI −2.02 to −0.73) for intra-operative pain, and pre-emptive oral analgesics (SMD = −0.77, 95% CI −1.21 to −0.33) for reducing post-operative pain in children receiving routine dental care. Conclusion: The GRADE results for these interventions were strong recommendation (IB) for their use, based on moderate evidence and their benefits far outweighing the harm, and they can be delivered readily with minimal training to reduce the pain experience of paediatric patients.